The Quest for Public Trust: The Limits of Information Access Reforms Based on the New Institutional Economics. The Case of Mexico. Issue 9 (28th July 2016) - Arellano-Gault, David
ABSTRACT: Mexico undertook a bold transparency reform 13 years back. This reform promised one objective: to increase citizens' trust in the government. However, trust in the Mexican government is still extremely low (and decreasing). In order to understand this situation the article argues that the contradiction is created by the logics of the New Institutional Economics (NIE) assumptions, the analytical base for this reform. NIE oversimplifies the social and political dynamics of public organizations, producing a paradox: in order to increase trust in government, citizens must have a structural distrust on their public organizations. The article proposes to go beyond NIE in order to actually increase trust in governments.